2011
DOI: 10.1007/978-3-642-23774-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Motion and Attention in a Kinetic Videoconferencing Proxy

Abstract: Abstract. Compared to collocated interaction, videoconferencing disrupts the ability to use gaze and gestures to mediate interaction, direct reactions to specific people, and provide a sense of presence for the satellite (i.e., remote) participant. We developed a kinetic videoconferencing proxy with a swiveling display screen to indicate which direction that the satellite participant was looking. Our goal was to compare two alternative motion control conditions, in which the satellite participant directed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…In the initial stage of this study, we assume one-to-one communication, thus aiming to contribute to the design of telepresence robots in order to support accurate joint attention between one remote participant and one local participant. Therefore, our findings might not be directly applicable to the design of a telepresence robot for assisting smooth turn-taking during remote multi-party meetings [25,26]. However, we believe that our findings can be part of a fundamental knowledge to understand various gaze-related phenomena that can be observed during such meetings.…”
Section: Introductioncontrasting
confidence: 49%
“…In the initial stage of this study, we assume one-to-one communication, thus aiming to contribute to the design of telepresence robots in order to support accurate joint attention between one remote participant and one local participant. Therefore, our findings might not be directly applicable to the design of a telepresence robot for assisting smooth turn-taking during remote multi-party meetings [25,26]. However, we believe that our findings can be part of a fundamental knowledge to understand various gaze-related phenomena that can be observed during such meetings.…”
Section: Introductioncontrasting
confidence: 49%
“…"Attention is fundamental to the flow of face-to-face conversation, " page 1 [92]. Each participant in an interaction project cues where their attention is directed.…”
Section: Quality Of Communication Measuresmentioning
confidence: 99%
“…For example, a turnable display resulted in a higher level of activity, perceived excitement of the speakers, level of attentiveness and engagement, and amount of turns per second during satellite-hub interaction when compared to interaction through a video conferencing system with a static display [92]. The study included sociometric measures, feedback from the pilot of the system, semi-structured, and several individually filled questionnaires.…”
Section: Quality Of Communication Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they showed that the 3D model resulted in an accurate perception of gaze direction, unlike the Mona Lisa gaze effect typically seen when using a 2D surface to display 3D face imagery. Sirkin et al developed a videoconferencing system that used a 2D display for the user's face, but the display could swivel to indicate gaze direction [13].…”
Section: Related Workmentioning
confidence: 99%